2011
DOI: 10.1002/jrs.3027
|View full text |Cite
|
Sign up to set email alerts
|

Surface characteristics of Ag‐doped Au nanoparticles probed by Raman scattering spectroscopy

Abstract: We have examined the surface characteristics of Ag-doped Au nanoparticles (below 5 mol% of Ag) by means of the surfaceenhanced Raman scattering (SERS) of 2,6-dimethylphenylisocyanide (2,6-DMPI) and 4-nitrobenzenethiol (4-NBT). When Ag was added to Au to form ∼35-nm-sized alloy nanoparticles, the surface plasmon resonance band was blue-shifted linearly from 523 to 517 nm in proportion to the content of Ag up to 5%. In the SERS spectra of 2,6-DMPI, the N-C stretching peak also shifted almost linearly from 2184 t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2014
2014

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 49 publications
0
1
0
Order By: Relevance
“…Kim and co‐workers studied the surface characteristics of Ag‐doped Au nanoparticles with Raman scattering. Their observations suggest that the surface content of Ag should increase almost linearly as a function of the overall mole fraction of Ag and, once the Au/Ag nanoparticles reach 5 mole% of Ag, their surfaces are fully covered with Ag, showing the same surface characteristics of pure Ag nanoparticles . In a related paper, these same investigators studied surface potential variation of gold nanoparticles by organic vapors as revealed by Raman scattering of 1,4‐phenylenediisocyanide.…”
Section: Nanomaterialsmentioning
confidence: 98%
“…Kim and co‐workers studied the surface characteristics of Ag‐doped Au nanoparticles with Raman scattering. Their observations suggest that the surface content of Ag should increase almost linearly as a function of the overall mole fraction of Ag and, once the Au/Ag nanoparticles reach 5 mole% of Ag, their surfaces are fully covered with Ag, showing the same surface characteristics of pure Ag nanoparticles . In a related paper, these same investigators studied surface potential variation of gold nanoparticles by organic vapors as revealed by Raman scattering of 1,4‐phenylenediisocyanide.…”
Section: Nanomaterialsmentioning
confidence: 98%